Software technologies : applications and foundations : STAF 2017 Collocated Workshops, Marburg, Germany, July 17-21, 2017, Revised selected papers /: applications and foundations : STAF 2017 Collocated Workshops, Marburg, Germany, July 17-21, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available